АВТОМОБИЛ ЙЎЛЛАРИДАГИ ТИРБАНДЛИКЛАР МУАММОЛАРИ ВА УЛАРНИ ОЛДИНИ ОЛИШНИНГ ЗАМОНАВИЙ ЙЎЛЛАРИ - Тажимуратов, У.Р.; Самадов, Ғ.А.; Тажимуратов, Р.О.; Жуманиёзов, Э.Х.; Тажимуратов, А.У. (SCIENCE and SOCIETY, 2023)
The article focuses on reducing intersection congestion, road traffic accidents and related fatalities. It also talks about the newly invented multi-functional road signs, their contribution to improving the quality of service and several other advantages.